Religiosity and deviance among college students in Türkiye: a test of ascetic theory - Jang, Sung Joon (Deviant behavior, 2023)
Although an inverse relationship between religion and deviance is empirically well-established in the western context, previous studies on Islam and deviance conducted in non-western countries are limited. To address this gap in deviance research, we hypothesized that individual religiosity would be inversely related to deviance with the inverse relationship being more likely for ascetic than anti-ascetic or secular deviance. To test this hypothesis, we applied ordinary least squares and logistic regression methods to analyze data collected from 2,005 survey participants of a Turkish public university student population. Regression results provided partial support for the hypothesis, as we found that religiosity was inversely related to both ascetic and secular deviance. The observed inverse relationship is noteworthy in that it was found in an institutionally secular, Muslim country. Implications of our findings are discussed.